Educational attainment across generations: The role of immigration background - Cobb-Clark, D.; Nguyen, Ha (Wiley-Blackwell Publishing Asia, 2012)
This paper analyses educational attainment among immigrant and native-born youth in Australia. We find that young Australians from non-English-speaking-background (NESB) immigrant families have an educational advantage over their English-speaking-background (ESB) immigrant and Australian-born peers. The educational advantages associated with immigrant parents’ higher educational attainment are counterbalanced by the disadvantages associated with immigrant families’ greater socioeconomic disadvantage, making endowment effects overall relatively unimportant in explaining the gap. Instead, most of the educational gap associated with immigration background stems from differences in the educational attainment of immigrant and native-born youths with the same characteristics. While immigrant parents do not have an enhanced ability to transmit their own educational advantage to their children, they are more effective in shielding their children from some of the negative educational consequences of socioeconomic disadvantage. Finally, immigrant youths’ residential patterns convey substantial educational advantages to them.